Letramentos em escritas de fé: as cartas dos devotos do Bom Jesus da Lapa - Elvina Perpétua Ramos Almeida (2021)
This work aimed to research what votive and ex-voto letters of Santuário Bom Jesus da Lapa, seen as literacy practices, portray in their discourses, considering the cultural, social and historic aspects around these written records. The study dialogues with several fields of study, such as culture and religiousness, literacy, written culture, and discursive perspectives to genre analysis. Santuário Bom Jesus, the space of field research, in the city of Bom Jesus da Lapa, center-west region of Bahia, Brazil, is a place of pilgrimage since the end of the 17th century. It holds examples of different types of votive objects, among them letters which we categorized as votive (wish), ex-voto (acknowledgement), and votive and ex-voto letter (wish and acknowledgement). The central axis of this research is the notion of literacy as a social practice, understanding written culture as a place to produce and attribute symbolic meanings and material practices, in the interface with genre notions and discursive practices. We adopted a methodology founded on the qualitative paradigm, based on ethnography principles. The instruments used to collect empirical data were: a) participant observation, with field notes, photos, and video recordings; b) semi-structured interviews, and; c) document analysis. We selected 100 letters, out of 250, to be analyzed, comprising our research corpus. We analyzed the letters based on categories, such as: most recurrent themes, how authors portray their trajectories on social, cultural, and historical frameworks; discursive strategies used to reach their intentions; cultural practices (rituals, oral genres) that are part of the delivery processes; senses and meanings granted to the letters by the authors and the Santuário; as well as the way to safekeep them, select, exhibit, and what is done with the letters. Regarding the specific and situated cultural scope, we needed to broadly understand the environment, the spaces, rituals, images, objects, and gestures that are a part of the practices in the Santuário, understood as a symbolic, social, cultural space and, above all, a sacred place devoted to Jesus, associated with miracles and expressions of believers‟ faith. The analysis allowed us to perceive the letter as a hybrid genre, marked by typical elements of orality. A mapping of the devotional texts have shown that there is a greater amount of exvoto letters, mainly thanking the cure of diseases. Besides this, women, identified by the authors‟ names, wrote, in first person, most of them. Among the most recurrent themes are: health, chemical addiction, work, study, and family relationships. The analysis allowed us to affirm that the letters portray an interface with the texts that constitute Church rituals, such as repetition of behaviors; the context of the Santuário and its symbols, as dispositives of faith, are key to the production of these writings. The genre highlights the subjects/authors discursively inserted in the religious space, stresses human historic and social conditions, and establishes itself as a way to disseminate information on current reality. Among the discursive particularities of votive and ex-voto letters is that authors address an interlocutor that is not on the terrestrial sphere, therefore implying a transcendental experience. Thus, writing establishes itself as a way to materialize the immaterial.